Analisis Pengungkapan Sosial dalam Laporan Keberlanjutan di PT Bukit Asam Tbk (PTBA) Periode 2022-2023 - Yuliana, Dila Putri; Giawa, Hidayatul Fadillah; Resti, Tengku (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This research aims to analyze the level of social disclosure in sustainability reports based on economic, environmental and social categories at PT. Bukit Asam Tbk in the 2022-2023 period. This research uses quantitative research methods using secondary data from sustainability reports and analyzed using descriptive methods. The research results show that economic performance is disclosed with the highest percentage, the second highest level is environmental performance and social performance is the performance category with the lowest percentage of disclosure. PT. Bukit Asam Tbk carries out quality communications based on the GRI-G4 sustainable reporting guidelines with a value of 70.33% percent and can be classified as partially implemented (Partially Applied).